Helicobacter pylori chronic gastritis updated Sydney grading in relation to endoscopic findings and H. pylori IgG antibody: diagnostic methods. Issue 4 (December 2016) - Hassan, Taha M.M.; Al-Najjar, Samia I.; Al-Zahrani, Ibrahim H.; Alanazi, Fadi I.B.; Alotibi, Malek G.
Abstract: Helicobacter pylori (Hp) inhabits the stomach of > 50% of humans and has been established as a major etiological factor in the pathogenesis of chronic gastritis, gastric atrophy, peptic ulcer disease, gastric adenocarcinoma, and gastric mucosa-associated lymphoid tissue lymphoma. The aim of this study was to provide unequivocal information about Hp-associated gastritis grading according to the Sydney grading system and to compare the histopathological features with the endoscopic findings and anti-Hp immunoglobulin (Ig)G serological status. This analytical study was conducted on 157 patients with dyspeptic gastritis. All patients underwent esophagogastroduodenoscopy, and antrum and corpus biopsies were taken. Blood samples were obtained from all participants. Different stains were performed on formalin-fixed, paraffin-embedded tissue blocks that included hematoxylin and eosin and Giemsa stain for histopathological interpretation. The endoscopic findings of gastritis were observed in 120 patients and most of them showed hyperemia (80 patients), whereas seven patients had normal appearing gastric mucosa. Histologically variable numbers of mononuclear inflammatory cellular infiltrates were seen in 150 cases (95.5%). Most of them showed Grade 1 gastritis (80 patients), whereas Grades 2 and 3 were found in 43 and 27 biopsies, respectively. Hp colonization was observed in most of the examined biopsies (93.7%). Hp-IgG seropositivity was found in 80.9% of cases and 19.1% were seronegative. The relationship between endoscopic and histological findings was significant ( p < 0.001).